Designing Attractive Web-Based Covid-19 Information System - Rafdhi, Agis Abhi; Radliya, Nizar Rabbi (Universitas Komputer Indonesia, 2023)
The World Health Organization (WHO) declared Coronavirus Disease 19 (COVID-19) to be a pandemic on March 13, 2020. Indonesia is one of the countries affected by COVID- 19, which spreads quite quickly. To support the government in making policies, an information system that can manage COVID-19 cases is needed. The purpose of this study is to design a prototype of an information system for Covid-19 cases in a city. This study employed descriptive analysis with a qualitative approach. In the meantime, the System Development Life Cycle Prototyping method of designing information systems employed an object-oriented methodology. The results show that information systems' development can provide actual information for the local government and society. This information system's main concept is to take advantage of the role of the puskesmas (Community Health Centers) from each sub-district to collect data directly from the community. After obtaining the data, it will be submitted to the sub-district officer in charge of inputting it into the system. The data that has been input will go through the verification stage by the surveyor. If appropriate, then the data will be published in the latest data update on that day to access the general public. The Covid-19 case information system's prototype can improve existing systems and provide input on renewable concepts in the procedures it carries out. In the end, this prototype of the information system exists as an actual and accurate, and reliable information medium to facilitate government decision-making at regional and national levels.